Comprehensive Review of Pharmaceutical Innovations: The Role of Pharmacists in Modern Healthcare Systems - Alyami , Sarran Mahdi H; Alswedan , Hadi Yahya H; Al Zamanan , Yasser Yahya S; Al-Harith , Masoud Musfar A Aba; Almahamedh , Hassan Saad H; Almakhalas , Abdulrahman Jaber B.; Lasloum , Saleh Muhammad H; Alrizq , Mesfer obaid Mana; Almakhlas , Mohammed Saidan S (Journal of Ecohumanism, 2024)
He found that advanced medical drugs are amongst the most defining features of modern healthcare systems, as they offer far better patient results than earlier technologies due to the introduction of distinct new therapies, better treatment of symptoms, and novel administration systems. These changes have also impacted pharmacists' roles, from simple mule dispensers to clinical experts in medication management, patient counseling, and decision-making. It aims to investigate the new pharmacopeia in pharmaceutical technological development and the new role of pharmacists in such changes. The paper discusses the concept of personalized medicine, the place and role of biologics biosimilar, and the increasing function of pharmacists in managing a vast number of related and interconnected processes of pharmacotherapy. Therefore, this paper aims to highlight through a synthesis of prior research, case-study investigations, and concept-based studies the role and contribution of pharmacists, particularly in balancing the therapeutic effectiveness of new drugs while dispersing related risks, adherence, and quality of life.